Homologous pairing in genetic recombination: formation of D loops by combined action of recA protein and a helix-destabilizing protein. - Shibata, T (1980)
Escherichia coli single-strand binding protein (SSB) or phage T4 gene 32 protein reduced the amount of recA protein required to catalyze the formation of D loops from double-stranded DNA and homologous single-stranded fragments. Neither SSB nor gene 32 protein alone catalyzed the formation of D loops, and excessive amounts of either protein, amounts that were sufficient to saturate the single strands, inhibited the formation of D loops completely. Both the stimulatory activity and the inhibitory activity of SSB resisted boiling, which is consistent with the known thermal stability of SSB, whereas the gene 32 protein was inactivated by heating. The formation of D loops in the presence of both recA protein and SSB required homologous DNA and ATP. Spermidine aided the combined action of SSB and recA protein in forming D loops, but Mg2+ alone was sufficient as a counterion.